Kemampuan Pemahaman Lintas Budaya Dalam Pembelajaran Membaca Melalui Flipped Learning Model - Nurming Saleh; Syukur Saud; Nursalam Nursalam (Seminar Nasional LP2M UNM, 2019)
Intercultural understanding skills in learning reading through the Flipped Learning Model (FLM). Learning a language is a conscious effort to improve the competencies that are the main target of a learning process, but indirectly learners will also be introduced to the culture of the language that is studied. FLM is an instructional didactic learning model that has a pillar of cultural benchmarking that is packed through the implementation of digital technology media that will facilitate learning both in the classroom and out of class. This study aims to obtain information on the ability to cross-cultural understanding in learning to read German through FLM. This research is a qualitative study and conducted in the German language education study Program Faculty of Language and Literature of Makassar State University with the number of samples as much as 25 people. Data is collected through field records, observations, interviews and reading ability tests to determine the cross-cultural understanding of students of the German language and analyzed qualitatively and by using the percentage technique. The results showed that FLM had a significant impact on student enthusiasm in reading learning. It is backed by a percentage of the cross-cultural understanding ability of 80.20%.